Genetic variability and associations in shankha pushpi (Convolvulus microphyllus Siebe ex. Spreng) - Lal, R K (Journal of Spices and Aromatic Crops, 2003)
Nature and amount of genetic variability, co-heritability, path-coefficients and associations were studied on eight economic traits in 52 genetic stocks of Shankha pushpi assembled from different states of India. Genotypic correlation was larger than phenotypic correlation for most of the traits. Days to 50% flowering was significantly and positively correlated with length of main branch and herb yield (g plot-1) at both genotypic and phenotypic levels but it was negatively correlated with leaf width at environmental level. Spread area and herb yield (g plot-t) were also significant and positively associ a ted at both genotypic and phenotypic levels but it was negatively associated with the main branch length at environmental level. Positive association was also recorded between main branch length and leaf width at genotypic level only. Negative associations were observed between primary branches and leaf width, leaf length and herb yield (g plot-1). All traits exhibited high heritability h2 (BS) (96.34-99.24%) except leaf width (37.02%) and days to 50% flowering (71.96%). Genetic advance was high for only spread area and herb yield (g plot-1). Highest direct contribution to herb yield was by days to 50% flowering (0.319) and spread area (0.245) followed by primary branches plant-1 (0.052) and main branch length (0.033). Days to 50% flowering indirectly contributed maximum to herb yield by main branch length. The association between spread area and leaf width showed maximum co-heritability (1.135) followed by that between leaf length and leaf width (1.114) and primary branches plant-1 and leaf width (1.072) and hence these traits may form a good selection criteria for improvement of herb yield.